2019
DOI: 10.3389/frobt.2019.00124
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Signatures and Hand Motion Intent Recognition for Wearable Assistive Devices

Abstract: Within the field of robotics and autonomous systems where there is a human in the loop, intent recognition plays an important role. This is especially true for wearable assistive devices used for rehabilitation, particularly post-stroke recovery. This paper reports results on the use of tactile patterns to detect weak muscle contractions in the forearm while at the same time associating these patterns with the muscle synergies during different grips. To investigate this concept, a series of experiments with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…SVM achieved the highest recognition accuracy in real-time mode, although it required the longest training and prediction time compared to kNN and DT methods [77]. SVM has also outperformed kNN, logistic regression and RF methods for recognition of grip action from an assistive tactile arm brace (TAB) worn on the forearm of participants [78]. However, in human activity recognition (HAR) with IMU data, RF methods showed to perform better compared to SVM, DT, NN, kNN and Naive Bayes methods [79].…”
Section: Traditional Machine Learning Methodsmentioning
confidence: 99%
“…SVM achieved the highest recognition accuracy in real-time mode, although it required the longest training and prediction time compared to kNN and DT methods [77]. SVM has also outperformed kNN, logistic regression and RF methods for recognition of grip action from an assistive tactile arm brace (TAB) worn on the forearm of participants [78]. However, in human activity recognition (HAR) with IMU data, RF methods showed to perform better compared to SVM, DT, NN, kNN and Naive Bayes methods [79].…”
Section: Traditional Machine Learning Methodsmentioning
confidence: 99%
“…A review of the databases showed that there is no comparable software; hence, it is difficult to compare our results with those of other authors. A review of four key databases, PubMed, WoS, Scopus, and Google Scholar, returned only four scientific articles in English with the keywords 'assistive device', 'stroke', and 'machine learning' [13][14][15][16]. The introduction of a second opinion or expert system into the selection process of assistive technologies, not only in post-stroke patients, seems to be a necessity, as this has been a research gap thusfar.…”
Section: Related Workmentioning
confidence: 99%
“… An example of FMG device with an array of eight force sensors (Tactile Arm Brace) placed on the able-bodied user. Adapted from [ 101 ], licensed under CC BY 4.0. …”
Section: Figurementioning
confidence: 99%